Adaptive frequency deviation improvement using a voltage-controlled storage inverter in a weak distribution network with a high penetration level of stochastic photovoltaic power - Li, Zhicheng; Chen, Jinyu; Zhang, Weijun; Chen, Dawei; Zhang, Shuling; Gao, Tongtong; Zhang, Wei; Wang, Zhenxiong (Frontiers in Energy Research, 2023)
With the fast increase of renewable energy sources in the user side, the strength of power grid is reduced, which may lead to lots of weak distribution network. The inertia of weak distribution network decreases greatly, which leads to poor voltage quality. It means that the voltage and frequency is distorted and deviated. Battery storage can balance the frequent power disturbance and enhance the frequency quality. However, it usually needs a central controller to dispatch the power in current-controlled mode or respond natively with fixed linear curve in voltage-controlled mode. The performance is not good when the power demand is in a wide range, which further deteriorates the frequency quality. To solve the problem, this paper proposes an adaptive frequency deviation improvement method of energy storage in voltage-controlled mode. This method can change the power output characteristics of the storage inverter according to the magnitude and trend of power demand, where both frequency deviation and changing rate are used to quantify the output power curve. A transfer function model for voltage-controlled storage inverter is set up for theoretical analysis. Then, with the model, an adaptive frequency deviation improvement method is proposed with fast response to power demand in a wide range. Finally, the results verify the effectiveness of the proposed method for frequency quality improvement with high penetration level of stochastic photovoltaic power.